Effective Topical and Oral Treatments for Skin Aging: Review - GONÇALVES, GISELE MARA SILVA; WENCESLAU, LAINA RAFAELA (Brazilian Journal of Implantology and Health Sciences, 2023)
The utilization of both systemic and topical treatments in dermatology with the expectation that their combination will enhance attributed benefits and provide preventive dermatology has gained interest. In order to identify effective combined treatments for skin aging, a systematic review was conducted (clinical trials), which comprehensively searched the Capes Journal Portal of E-Journals. Out of the 4543 articles evaluated, only 24 were deemed eligible for final analysis. The findings were characterized as clinical studies that evaluated various combinations of treatments. It was concluded that the efficacy of collagen peptides, antioxidants, moisturizers, and lifestyle changes in mitigating skin aging resulted in improvements in the firmness, elasticity, hydration, and antioxidant protection of human skin.